Comparison of short-term effectiveness between unilateral biportal endoscopic and MED-assisted transforaminal lumbar interbody fusion for mild single-segment lumbar spondylolisthesis - Yu He; Jin-wang Liu; Miao Fang; Ming-juan He; Ding Hu; Xiao-ping Xu (BMC Musculoskeletal Disorders)
Abstract Objectives The purpose of this study was to compare the short-term clinical efficacy of unilateral biportal endoscopic transforaminal lumbar interbody fusion (UBE-TLIF) versus minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) with microendoscopic discectomy (MED) for lumbar spondylolisthesis. Methods The patients were divided into MIS-TLIF group and UBE-TLIF group according to the surgical procedures. The two groups were compared in terms of surgery-related parameters, postoperative functional scores and complications. Results Compared with the MIS-TLIF group, the UBE-TLIF group had a longer surgical time, less intraoperative and postoperative blood loss, and less length of stay (LOS) (p < 0.001). Comparison of visual analog scale (VAS) scores and Oswestry Disability Index (ODI) scores at each postoperative time point between the two groups showed no statistically significant difference (p > 0.05). At the final follow-up, the lumbar lordosis (LL) and Cobb angle were improved in both groups compared with the preoperative period, but the difference between the pre- and postoperative of the two groups was not statistically significant (p > 0.05). The intervertebral fusion of the two groups was compared at each postoperative time point, and the difference was not statistically significant (p > 0.05). During the follow-up period, there was no statistically significant difference between the two groups in terms of complication rate (p > 0.05). Conclusion In the treatment of mild lumbar spondylolisthesis, UBE-TLIF can achieve satisfactory short-term results comparable to MED-assisted MIS-TLIF. Compared with MED-assisted MIS-TLIF, UBE-TLIF has the advantages of less perioperative bleeding, shorter LOS, and faster early postoperative recovery, despite the longer surgical time.